2020
DOI: 10.21608/ejdr.2019.16947.1041
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Some Tomato Genotypes Under Greenhouse Conditions

Abstract: valuation of genotypes under greenhouse conditions comes in the first order for Tomato Breeding Program of Desert Research Center (DRC). A major objective of the program has been to develop breeding lines that possess characteristics needed in high-performing hybrid varieties at greenhouse conditions. The twelve genotypes indeterminate were transplanted in a greenhouse at Baloza Station, DRC, North Sinai, during 2016/2017 and 2017/2018 seasons. The experimental design was randomized complete block design with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 6 publications
2
1
0
Order By: Relevance
“…This interaction between environmental and tomato hybrids is expected to have a significant impact on future breeding programs. These results are in line with those obtained by Alam et al (2010), Singh et al (2014), Kumar et al (2015), Singh et al (2019) and Bayomi et al (2020).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…This interaction between environmental and tomato hybrids is expected to have a significant impact on future breeding programs. These results are in line with those obtained by Alam et al (2010), Singh et al (2014), Kumar et al (2015), Singh et al (2019) and Bayomi et al (2020).…”
Section: Resultssupporting
confidence: 93%
“…Generally, all hybrids in which yield per plant were higher than the grand mean of the two locations. Similar ranges of genetic differences for yield in different tomato hybrids had also been reported by Alam et al (2010), Jindal et al (2015, Kumar et al (2015), Singh et al (2019) and Bayomi et al (2020). Phookan et al (1998) found that heritability values were high for fruit set percentage and total yield/plant.…”
Section: Yield Per Plant (Kg)supporting
confidence: 69%
See 1 more Smart Citation